Risk-reducing salpingo-oophorectomy, natural menopause, and breast cancer risk: an international prospective cohort of BRCA1 and BRCA2 mutation carriers - Mavaddat, Nasim; Antoniou, Antonis C; Mooij, Thea M; Hooning, Maartje J; Heemskerk-Gerritsen, Bernadette A; Noguès, Catherine; Gauthier-Villars, Marion; Caron, Olivier; Gesta, Paul; Pujol, Pascal; Lortholary, Alain; Barrowdale, Daniel; et al. (Breast cancer research, 2020)
BACKGROUND: The effect of risk-reducing salpingo-oophorectomy (RRSO) on breast cancer risk for BRCA1 and BRCA2 mutation carriers is uncertain. Retrospective analyses have suggested a protective effect but may be substantially biased. Prospective studies have had limited power, particularly for BRCA2 mutation carriers. Further, previous studies have not considered the effect of RRSO in the context of natural menopause. METHODS: A multi-centre prospective cohort of 2272 BRCA1 and 1605 BRCA2 mutation carriers was followed for a mean of 5.4 and 4.9 years, respectively; 426 women developed incident breast cancer. RRSO was modelled as a time-dependent covariate in Cox regression, and its effect assessed in premenopausal and postmenopausal women. RESULTS: There was no association between RRSO and breast cancer for BRCA1 (HR = 1.23; 95% CI 0.94-1.61) or BRCA2 (HR = 0.88; 95% CI 0.62-1.24) mutation carriers. For BRCA2 mutation carriers, HRs were 0.68 (95% CI 0.40-1.15) and 1.07 (95% CI 0.69-1.64) for RRSO carried out before or after age 45 years, respectively. The HR for BRCA2 mutation carriers decreased with increasing time since RRSO (HR = 0.51; 95% CI 0.26-0.99 for 5 years or longer after RRSO). Estimates for premenopausal women were similar. CONCLUSION: We found no evidence that RRSO reduces breast cancer risk for BRCA1 mutation carriers. A potentially beneficial effect for BRCA2 mutation carriers was observed, particularly after 5 years following RRSO. These results may inform counselling and management of carriers with respect to RRSO.
Keywords: mutace; dospělí; nádory prsu; mezinárodní agentury; Female; chování snižující riziko; Adult; ženské pohlaví; BRCA1 Protein; lidé; Breast Neoplasms; Mutation; menopauza; protein BRCA2; International Agencies; kohortové studie; Incidence; Cohort Studies; Risk Reduction Behavior; prospektivní studie; incidence; Prospective Studies; protein BRCA1; Menopause; lidé středního věku; Salpingo-oophorectomy; Middle Aged; BRCA2 Protein; salpingo-ooforektomie; Humans